Perbedaan Kecepatan Pengembangan Paru Sebelum dan Sesudah Latihan Pernapasan Diafragma dalam Upaya Mempercepat Pelepasan Water Seal Drainage (WSD) - Rosalina Rosalina; Sukarno Sukarno; Yunita Galih Yudanari (Indonesian Journal of Nursing Research (IJNR), 2018)
An  Pleural effusion is an excessive accumulation of fluid, blood or water in the pleural cavity which will cause the increase of shortness of breath because of the decreasing space for lung expansion. One of the efforts  to reduce the complaints of shortness of breath is by insertion of water seal drainage. Water Seal Drainage (WSD) is a medical action performed to remove air or fluid from the pleural cavity. The patient's ability to breathe effectively is an indicator to release WSD. This study generally aims to determine the effectiveness of diaphragmatic breathing exercises on the speed of lung expansion in patients with  water seal drainage insertion. The research design  was pre experiment with  pre test - post test group design. The population in this study were patients with insertion of  WSD who were admitted to  Dr. Muwardi Surakarta Hospital. The sampling technique was purposive sampling. The number of samples were 16 respondents. To measure lung expansion, the indicator used  Peak Expiratory Flow Rate  as measured by  peak flow meter. Data analysis used dependent  t-test. The results show that there are differences in the speed of lung expansion  in patients with WSD insertion before and after diaphragmatic breathing exercises with  p-value of  0.0001. Suggestion  for nurses to be able to train diaphragmatic breathing exercise in patients with WSD insertion  increase  lung expansion so that WSD can be released and the risk of infection can be reduced.